2022
DOI: 10.3390/rs14102375
|View full text |Cite
|
Sign up to set email alerts
|

Can Forel–Ule Index Act as a Proxy of Water Quality in Temperate Waters? Application of Plume Mapping in Liverpool Bay, UK

Abstract: The use of ocean colour classification algorithms, linked to water quality gradients, can be a useful tool for mapping river plumes in both tropical and temperate systems. This approach has been applied in operational water quality programs in the Great Barrier Reef to map river plumes and assess trends in marine water composition and ecosystem health during flood periods. In this study, we used the Forel–Ule colour classification algorithm for Sentinel-3 OLCI imagery in an automated process to map monthly, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 34 publications
(100 reference statements)
2
11
1
Order By: Relevance
“…However, the optical water type maps produced provided important information about water turbidity gradients in the study area, as well as information about their spatial and seasonal variability for the first time. The colour of waters is increasingly used as used an efficient optical feature to cluster OWTs in both inland and marine waters and to assess water quality patterns and trends (e.g., [51][52][53][54][55][56][57]). This study reiterated the potential of using a qualitative colour clustering approach with satellite images in large, complex and/or data-poor regions, where more classical quantitative remote sensing methods are limited by the lack of available field data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the optical water type maps produced provided important information about water turbidity gradients in the study area, as well as information about their spatial and seasonal variability for the first time. The colour of waters is increasingly used as used an efficient optical feature to cluster OWTs in both inland and marine waters and to assess water quality patterns and trends (e.g., [51][52][53][54][55][56][57]). This study reiterated the potential of using a qualitative colour clustering approach with satellite images in large, complex and/or data-poor regions, where more classical quantitative remote sensing methods are limited by the lack of available field data.…”
Section: Discussionmentioning
confidence: 99%
“…Water colour is the result of the presence of marine constituents (SSC, chlorophyll-a [Chl-a] and coloured dissolved organic matter [CDOM]) and their interactions with solar irradiance [49]. Several studies have reported that there is a quantifiable relationship between water colour and water quality parameters, including a strong relationship with turbidity [50][51][52]. Accordingly, water colour is regarded as a simple yet efficient optical parameter for assessing water quality changes [14,53].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of the river plume from the satellite-derived FUI values was determined using established techniques [29,30]. All the monthly median FUI layers were reclassified…”
Section: Spatial Plume Frequency Mapsmentioning
confidence: 99%
“…In turn, the offshore assessment areas used to assess eutrophication under the OSPAR Comprehensive Procedure [18] can extend to larger areas, diluting the impact of these coastal waters. Recent work [29] has identified plume extents from Liverpool Bay that extend further than the WFD assessment areas, but are still relatively nearshore. The nutrient and plankton dynamics in these plume areas need to be considered in their own right, and not as the edge of the WFD or the initial zone in the OSPAR offshore area [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation